Achieving high-energy density and superior cyclic stability in flexible and lightweight pseudocapacitor through synergic effects of binder-free CoGa2O4 2D-hexagonal nanoplates. (November 2020) - Javed, Muhammad Sufyan; Shah, Syed Shoaib Ahmad; Najam, Tayyaba; Siyal, Sajid Hussain; Hussain, Shahid; Saleem, Muhammad; Zhao, Zhijuan; Mai, Wenjie
Abstract: Highly flexible pseudocapacitors (PCs) have great potential in modern electronics such as portable and wearable devices. However, they are not yet mature enough to reach the market due to low energy density. In this study, for the first time, we are reporting an efficient synergetic approach by optimizing the feeding ratio of cobalt:gallium (Co:Ga) with a binder-free architecture composed by novel hexagonal-shaped nanoplates on carbon cloth (CC) substrate with high surface area to achieve high-energy electrode for asymmetric supercapacitor (ASC). Owing to the integrated strengths including enhanced electronic/ionic transportation and structural stability, the optimized sample with feeding ratio of Co:Ga = 1:2 (Co1 Ga2 O4 @CC) electrode exhibited excellent charge storage performance, including high capacitance of 1525 F g −1 (915 C g −1 ) at 5 A g −1 with superb rate-capability and superior cycling stability of 95% up to 10000 cycles. The charge storage mechanism was analyzed using typical electroanalytical methods and ex-situ XPS analysis, which reveals the hybrid-type charge storage characteristics in the aqueous electrolyte. Furthermore, the all-solid-state flexible asymmetric supercapacitors (Co1 Ga2 O4 @CC||AC@CC-ASC) were assembled and explored their energy storage properties. The Co1 Ga2 O4 @CC||AC@CC-ASC shows good performance by achieving a high capacitance of 239 F g −1 (382 C g −1 ) at 1.5 A g −1 and can be operated at an extended potential window of 0.0–1.6 V. The Co1 Ga2 O4 @CC||AC@CC-ASC also demonstrates interesting features such as light-weight (491.43 mg), ultra-thin (0.08 cm), high-energy and power densities (84 Wh kg −1, 1.85 Wh cm −3 at the power density of 1200 W kg −1, 26.4 W cm −3 ), and excellent flexibility. Our new approach, anchoring the CoGa2 O4 hexagonal nanoplates on the highly flexible carbon cloth substrate, may provide useful insights into the reaction mechanism of high-energy electrode materials for prompting energy storage applications. Graphical abstract: To accomplish the efficient and high-performance pseudocapacitors, electrochemically active materials with multi-component and rational morphological architectures are proposed. The Co1 Ga2 O4 @CC||AC@CC-ASC demonstrates interesting features such as light-weight (491.43 mg), ultra-thin (0.08 cm), high-energy and power densities (84 Wh kg −1, 1.85 Wh cm −3 at the power density of 1200 W kg −1, 26.4 W cm −3 ), and excellent flexibility. Image 1 Highlights: Binder-free CoGa2 O4 @CC hexagonal nanoplates are directly fabricated on the highly flexible carbon cloth substrates. The optimized Co1 Ga2 O4 @CC exhibits high capacitance of 1525 F g −1 (915 C g −1 ) at 5 A g −1 with superb rate-capability. The Co1 Ga2 O4 @CC||AC@CC-ASC shows good performance by achieving a high capacitance of 239 F g −1 (382 C g −1 ) at 1.5 A g −1 . The Co1 Ga2 O4 @CC||AC@CC-ASC possesses light-weight (491.43 mg), ultra-thin (0.08 cm) and excellent flexibility.